2022
DOI: 10.1039/d2cp00666a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of proton-coupled electron transfer reactions in lysine-containing alpha-helixes: alpha-helixes promoting long-range electron transfer

Abstract: Proton-coupled electron transfer (PCET) reaction plays an important role in promoting the progresses of many biological and chemical reactions. Usually the rate of PCET reaction increases with the increase of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Apart from the typical electro-active proteins (e.g., cytochrome c and Complex III), 23 , 24 amide groups in common protein-like substances also serve as the sites for electron transfer. 25 It was reported that applying electric potential induced the polarity of amide groups to promote the electron transfer of protein-like substances. 26 The polarization of C=O of amide groups and depolarization of the N−H groups in the sludge benefited the breaking and bonding of H-bonds to transport electrons via coupling with H motions.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the typical electro-active proteins (e.g., cytochrome c and Complex III), 23 , 24 amide groups in common protein-like substances also serve as the sites for electron transfer. 25 It was reported that applying electric potential induced the polarity of amide groups to promote the electron transfer of protein-like substances. 26 The polarization of C=O of amide groups and depolarization of the N−H groups in the sludge benefited the breaking and bonding of H-bonds to transport electrons via coupling with H motions.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in our previous work, c -Cyts, as a typical electroactive protein, played an electron transfer role in reversing EET . As a protein-like substance, the amide group could also act as a momentous electron transfer site first discovered in MES of ammonia . It was reported that an applied electric potential could induce amide group polarization and provide a motive force for electron hopping between proteins, in which the amide group could function as a relay station for electron transfer .…”
Section: Results and Discussionmentioning
confidence: 75%
“…11 As a protein-like substance, the amide group could also act as a momentous electron transfer site first discovered in MES of ammonia. 56 It was reported that an applied electric potential could induce amide group polarization and provide a motive force for electron hopping between proteins, in which the amide group could function as a relay station for electron transfer. 57 C−N and C�O were essential active sites in protein-like substances involved in electron transfer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%